United Republic of Tanzania : United Republic of Tanzania: Fifth Review Under the Policy Support Instrument-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Tanzania's Fifth Review Under the Policy Support Instrument (PSI). Tanzania's macroeconomic performance remains strong. Economic growth was robust during the first half of 2016. Inflation came down below the authorities' target of 5 percent and is expected to remain close to the target, while the external current account deficit was revised down on account of lower imports of capital goods. Nevertheless, there are risks that could adversely affect economic growth going forward, emerging from the currently tight stance of macroeconomic policies, slow implementation of public investment, and private sector uncertainty about the government's new economic strategies. The IMF staff recommends completion of the fifth review under the PSI.